Keanekaragaman Jenis Flora Epifit Di Hutan Kota Pekanbaru, Provinsi Riau dan Kajian Kekerabatannya - Nery Sofiyanti (Jurnal Biologi Universitas Andalas, 2019)
The city forest of Pekanbaru, Riau Province has many host trees for epiphytic flora. This study aimed to identify the epiphytic flora on tress of forest city Pekanbaru. Samples were collected from the field using exploration method. The morphological characters were scored and analysed to construct dendrogram using NTSyst 2. A total of 35 epiphytic floras were identified in this study, and consisted of mosses (12 species), ferns (21 species) and seed plants (2 species). Dendrogram showed that the examined species clustered based on the similarity of morphological characters